Line‐transient enhancement techniques for multi‐path hybrid DC–DC converter with <1% output overshoot/undershoot. Issue 25 (3rd October 2022) - Li, Huihua; Ma, Qiaobo; Jiang, Yang; Law, Man‐Kay; Mak, Pui‐In; Martins, Rui P.
Abstract: This letter presents two transient enhancement techniques for multi‐path switched‐capacitor‐inductor (MP‐SCI) hybrid DC–DC converters to eliminate the line‐transient‐induced voltage coupling to the converter output. Since the existing input‐feedforward method is hard to apply to the MP‐SCI converter, the proposed techniques tackle the intrinsic hard‐charging property with the MP‐SCI topology, preventing the line‐coupling current through topology operation reconfiguration and power‐switch modulation. The proposed controller also achieves adaptive line‐transition detection and automatic flying‐capacitor voltage balancing, ensuring a fast line regulation feature. Implemented with an MP‐SCI topology for a 9 to 14 V‐input to 5 V‐output conversion, the proposed control techniques provide an output ( V OUT ) overshoot and undershoot as low as 0.5% of the output DC level under a 3‐V input voltage step. From the simulation, the corresponding output variation reduction can be more than 94% when compared with the existing MP‐SCI operations. Besides, the proposed controller is compatible with a voltage‐mode (VM) V 2 pulse‐width modulation (PWM) function, achieving a fast load‐transient recovery in six switching cycles and a V OUT variation of 75 mV at a 5 V DC level under a 0‐to‐3 A load step. The peak conversion efficiency can be as high as 95.5%, and the targeted load current delivery is up to 3 A. Abstract : This letter presents two transient enhancement techniques for multi‐path MP‐SCI hybrid DC–DC converters to eliminate the line‐transient‐induced voltage coupling to the converter output. The proposed techniques tackle the intrinsic hard‐charging property with the MP‐SCI topology, preventing the line‐coupling current through topology operation reconfiguration and power‐switch modulation. The implemented converter achieves adaptive line‐transition detection and automatic flying‐capacitor voltage balancing, ensuring a fast line regulation and realizing an output overshoot and undershoot as low as 0.5% of the DC level.